Negative transconductance in multi-layer organic thin-film transistors. (9th November 2018) - Luo, Zhongzhong; Cao, Yujie; Liu, Jinyu; Li, Yimeng; He, Daowei; Shi, Yi; Hu, Wenping; Dong, Huanli; Wang, Xinran
Abstract: Negative transconductance (NTC) refers to the phenomenon of the N-shape transfer characteristic appearing with a current peak and valley. It has been extensively studied in the past few decades due to its applications in logic and memory devices. Here, we observe unique antibipolar transfer characteristics and NTC behavior in multi-layer 2, 6-diphenyl anthracene organic thin-film transistors grown on h -BN, which is due to the vertical potential barrier between the charge accumulation region near the substrate and the neutral bulk region under the contacts. The applied extrinsic electric field could effectively modulate the barrier height, resulting in a competition for charge carrier transport between lateral and vertical directions. Based on the NTC and antibipolar properties, a frequency doubler has been fabricated on a single transistor, which provides a new building block for organic logic circuits.